Adapting Home Educated Learning: The Creation of A Thriving Minority Islamic Education in Blackburn, England - Hanani, Nurul; Albshkar, Hajer Abdallah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2024)
This research elaborates on the learning strategy at Tauheedul Islam Girls’ High School and Sixth Form College (TIGHS) in Blackburn, England in adapting to government policies and minority conditions. The British government policy that gives autonomous space to formulate the curriculum to Islamic schools to develop a home educated-based curriculum, where learning schedules, materials and outcomes are directed at integrated Islamic teachings. The phenomenon of stereotypes and binaries against minority Islamic schools can be converted into a contributive solution. This research wants to reveal the strategy and leadership of al-Hijrah Islamic school using a qualitative approach. Data is taken documentatively supported by secondary sources in the form of report sources. The findings show that in order to adapt to distortive government policies, TIGHS conducts value adaptation, namely uniting academic principles with Islamic teachings by implementing home educated in the curriculum. The home educated curriculum is based on student needs, where material that is not taught in formal classes, can be continued at home with tutors, such as skills, academics and Islam. The implication of home educated is that students can gain life experience which is manifested in mindset and social behavior.